Nucleotide sequence and regulation of the Escherichia coli gene for ferrienterobactin transport protein FepB. - Elkins, M F (1989)
The Escherichia coli fepB gene encodes a periplasmic protein required for ferrienterobactin transport; four fepB-related polypeptides are resolved by standard sodium dodecyl sulfate-polyacrylamide gel electrophoresis. In vitro DNA-directed protein-synthesizing systems and experiments with the inhibitors dinitrophenol, carbonyl cyanide m-chlorophenylhydrazone, and ethanol demonstrated that the initial fepB translation product is processed. The nucleotide sequence of fepB and neighboring regions was determined. The predicted proFepB has a molecular weight of 34,255, consists of 318 amino acids, and is devoid of cysteine residues. A leader peptide is present, as are three possible leader peptidase cleavage sites after positions 22, 23, and 26. The upstream regulatory region included a Fur box, indicating that fepB is iron regulated, which was verified by RNA dot blot experiments. The regulatory region included a 68-amino-acid open reading frame (ORF) that encompassed a sequence capable of forming a large stem-and-loop structure. Indirect evidence indicated that this ORF must be translated for fepB transcription to occur. Six copies of the nonomer CCCTC(A/T)CCC or its invert were present in the stem-and-loop region. An ORF of unknown significance was found downstream from fepB; its product would have a molecular weight of 18,036 and be rich in proline and alanine. Processing of proFepB remains unclear, but the appearance of the three smaller members of the FepB family required the action of leader peptidase and the presence of the entire fepB gene.